Explaining the concepts and examples of conflict of interest and its management in the medical laboratory system of Iran: A scoping review - Hossein Dargahi; Mahdi Kooshkebaghi; Nikzad Isazadeh (Wolters Kluwer Medknow Publications, 2024)
The occurrence of conflict of interest (CoI) is assumed to be a big challenge facing all healthcare sectors, including the medical laboratory system (MLS). Therefore, this study aimed to explain the concepts and examples of CoI and its management within this system. This scoping review was fulfilled in 2023 in Iran. To this end, the Persian and English keywords of this study were searched on the Persian and English databases based on the Medical Subject Headings (MeSH) and the Arksey and O'Malley methodological framework. All retrieved articles were then imported into EndNote X8, and their quality was evaluated via the Mixed Methods Appraisal Tool (MMAT). In total, 104 articles, of 6875 sources extracted, published from 2000 to 2023, were recruited following the identification and screening stages. Most articles had reported the maximum number of CoI examples in the MLS in diverse nations, including Iran, particularly in terms of structural, financial, objective, and subjective issues and primary and secondary interests among policymakers and higher-ranking managers of the healthcare system. Currently, CoI in healthcare systems, including the MLS, is unavoidable, but the best strategy, in preference to removing this situation, is to manage it under potential conditions before its occurrence and conversion into corruption. In view of that, it is recommended to provide effective training programs, increase transparency at work, facilitate compliance with professional guidelines, reform organizational structures and processes in the public sector, and establish policies best suited to manage CoI in the MLS of Iran.